2017
DOI: 10.1111/sjop.12399
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of tattooing in Norway: A large‐scale cross‐sectional study

Abstract: To our knowledge, no previous large-scale study has examined the prevalences and correlates of having only easily concealed tattoos, or readily visible tattoos. We conducted an exploratory online survey in Norway asking 15,654 (6,151 females) persons aged 16-91 (m = 33.65 ± 12.27) about various demographic, sports, substance use, mental health, personality, and tattooing questions. The estimated prevalence of tattooing was 20.8% (females: 23.8%, males: 17.9%), of which 13.3% had readily visible tattoos. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
3
8
0
1
Order By: Relevance
“…Our finding associating males with higher willingness towards performance enhancement and females with higher willingness towards body modification is consistent with our previous finding (25). It is also in line with the preponderance of literature on gender/sex differences in performance enhancement (6,7) and body modification (29,30). Additionally, our finding that younger persons show higher willingness towards performance enhancement and body modification corroborates previous findings (26,37) and the perspective that human enhancement is an element or fountain of contemporary youth culture and identity (1,10,38).…”
Section: Demographic and Physical Appearance Correlates Of Willingnes...supporting
confidence: 91%
See 1 more Smart Citation
“…Our finding associating males with higher willingness towards performance enhancement and females with higher willingness towards body modification is consistent with our previous finding (25). It is also in line with the preponderance of literature on gender/sex differences in performance enhancement (6,7) and body modification (29,30). Additionally, our finding that younger persons show higher willingness towards performance enhancement and body modification corroborates previous findings (26,37) and the perspective that human enhancement is an element or fountain of contemporary youth culture and identity (1,10,38).…”
Section: Demographic and Physical Appearance Correlates Of Willingnes...supporting
confidence: 91%
“…In line with the stimulation (20) theory of tattooing (21), and evidence that higher scores on extraversion predict higher odds of having a tattoo (29) or contemplating getting a body piercing (40), we found that higher extraversion is associated with higher willingness towards body modification. An explanation for this finding is that higher scores on excitement/sensation seeking, a facet of extraversion (19), have been associated with a higher tendency towards body modification (11,39).…”
Section: Personality and Willingness Towards Performance Enhancement ...supporting
confidence: 87%
“…Subpopulations such as former power elite athletes [8, 9], recreational athletes [4], injecting drug users [10, 11] and arrestees/prisoners [12, 13] report higher lifetime AAS use than the general population. In Norway, life time AAS use is estimated to be about 2–3% among men and less than 1% among women [14] and current AAS use is found to be 0.6% in an online survey of self-selected participants [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our study suggests that tattooing is becoming more mainstream, which is in-line with previous literature. 2 We show that 5.9% of tattooed individuals report adverse reactions, which is high considering our focus on well-defined clinical symptoms. Potentially this restricted range of reactions from our questionnaire was a study limitation, resulting in an underestimation of the prevalence of tattoo-associated problems.…”
Section: Adverse Reactions To Tattoos In the General Population Of Denmarkmentioning
confidence: 74%